Performance of biomass pellets in domestic combustion systems - Maldonado, Felix Ricardo Charvet (2018)
In recent years the use of biomass pellets as an alternative energy source has experienced steady growth. The most widespread process for thermochemical conversion of biomass is combustion. Standardized commercial pellets and non-commercial non-standardized biomass pellets were used in this work. Eight types of biomass pellets were tested during combustion experiments in a pellet stove with a nominal power of 9.5 kWth, and the operating conditions were characterized. The stove used was a Solzaima model Alpes made in Portugal, a technology used for domestic heating. In order to monitor and acquire the experimental data during the combustion process, an interface software was developed. The work focused on characterizing the operating parameters such as the combustion temperature at five locations distributed along the combustion chamber and the chimney, the biomass fuel consumption, the flow rate of combustion air, the stoichiometric air needs, the excess fuel-air ratio, and the flue gas composition. Carbon balance was evaluated for every biomass pellets tested to determine the carbon conversion efficiency. It was observed that the physical and chemical characteristic of the pellets and the feeding system of the stove which does not provide a true continuous and uniform feeding have a direct influence over the operating parameters and therefore, in the composition of the exhaust gases. In some cases, gaseous pollutant emissions overpassed the limits set by Portuguese regulations. Also, it was observed that the shut-down procedure of the stove created combustion conditions that promote the emission of pollutants related to incomplete combustions such CO, C2H6, and CH4. Characteristics of pellets such as the high ash or moisture content were identified as unfavorable.